Pengaruh Kualitas Produk, Persepsi Harga, dan Citra Merek Terhadap Keputusan Pembelian Konsumen Richeese Factory di Surabaya - Ardiansyah Putra; Ugy Soebiantoro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the effect of product quality, perceived price, and brand image on purchase intention in consuming product of Richeese Factory in Surabaya. This research uses Partial Least Square (PLS) software as the media to anakyze the data and quantitative method is used in this research. Total sample used is 102 respondent obtained with non probability sampling method and purposive sampling approach. Questionnaire presented in google form and distributed to respondents as the media to obtain research data. The result of this research interpret that the better product quality, perceived price, and brand image, the greater the trust in customer’s mind to decide to purchase Richeese Factory products.